Peran Bakteri Rizhobium dalam Peningkatan Kesuburan Tanah dan Produktivitas Tanaman - Mendrofa, Ernidar; Lase, Natalia Kristiani (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
This study aims to determine the role of rhizophregal bacteria in increasing soil fertility and plant productivity. This type of research is a qualitative research that uses the literature review method. Research data sources include books, scientific articles. The main sources of articles are from various journals and indexed on the Google Scholar database. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the role of Rhizobium in increasing soil fertility is very important. Through the process of nitrogen fixation and soil quality improvement, these bacteria not only function to support plant growth, but also contribute to the sustainability of agricultural practices themselves. Therefore, the use of Rhizobium as a biofertilizer is a smart and strategic step to increase agricultural yields while maintaining the sustainability and health of soil ecosystems